The party of order : the conservatives, the state, and slavery in the Brazilian monarchy, 1831-1871 - Needell, Jeffrey D. (Stanford University Press, 2006)
Analyzes Brazil's monarchy, which adapted European ideas and practices to a Creole plantation society that was traditionally based on African slavery. This study focuses upon the Conservatives, who represented the sugar and coffee elites in reconstructing the nation's state as a strong, representative constitutional monarchy in troubled times.